2015
DOI: 10.1038/jid.2014.328
|View full text |Cite
|
Sign up to set email alerts
|

Activin A Is Anti-Lymphangiogenic in a Melanoma Mouse Model

Abstract: Melanoma spreads primarily to the sentinel lymph nodes, and its risk correlates with lymphangiogenesis, which is mainly driven by vascular endothelial growth factor (VEGF)-C. However, anti-lymphangiogenic factors are poorly characterized. We have shown in a melanoma model that Wnt1 reduces lymphangiogenesis by reducing VEGF-C expression. Screening this model for additional potentially anti-lymphangiogenic factors identified increased activin A expression and reduced expression of the antagonist, follistatin (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 48 publications
(49 reference statements)
2
24
0
Order By: Relevance
“…Melanoma cell lines and tumors also frequently express Activin-A (Heinz et al, 2015, Hoek et al, 2006. Activin-A stimulates the same SMAD transcription factors as TGFβ, even though it derives from distinct precursor dimers encoded by the Inhibin βA (INHβA) gene and binds distinct complexes of the Activin/Nodal type I and II receptors Acvr1b/ALK4 or Acvr1c/ALK7 and Acvr2 (reviewed in Hedger et al, 2011, Sozzani and Musso, 2011, Walton et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melanoma cell lines and tumors also frequently express Activin-A (Heinz et al, 2015, Hoek et al, 2006. Activin-A stimulates the same SMAD transcription factors as TGFβ, even though it derives from distinct precursor dimers encoded by the Inhibin βA (INHβA) gene and binds distinct complexes of the Activin/Nodal type I and II receptors Acvr1b/ALK4 or Acvr1c/ALK7 and Acvr2 (reviewed in Hedger et al, 2011, Sozzani and Musso, 2011, Walton et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Cytostatic and proapoptotic signaling by Activin-A has also been reported in human melanoma cell lines, although this activity is counteracted by the secreted antagonist Follistatin (FST-1) (Stove et al, 2004). Immunohistochemical analysis detected Activin-A staining in superficially spreading melanoma, whereas benign nevi and metastatic lesions showed elevated expression of Follistatin (Heinz et al, 2015). Interestingly, however, gain of transgenic Activin-A expression in the A375 human melanoma xenograft model did not alter tumor growth or metastasis, even though it reduced tumor lymphangiogenesis, a risk factor of poor prognosis (Heinz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in prostate and breast cancer ActA demonstrated tumor suppressive effects, while in lung and HNSCC, ActA expression correlated with increased proliferation and poor prognosis (38). ActA is also an anti-lymphangiogenic factor in melanoma (39). Although ActA levels were reported to be increased in patients with breast cancer (40) and in some mouse tumor models (41), new data showed that ActA protein in lung adenocarcinoma tissue was significantly lower than in normal lung tissue (42) and ActA may inhibit proliferation of breast cancer cell lines (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that ActA can activate autocrine and paracrine signaling affecting crosstalk between the epithelial compartment and the surrounding microenvironment (45) in a cell-type and context-dependent manner supporting or inhibiting tumor development (38). Without better understanding the controversial role of ActA in cancer, the use of ActA as a systemic pharmacological agent appears not suitable (39). At the same time, this justifies investigations into utilization of ActA potential to modulate cancer vaccines ex vivo for improving their efficacy.…”
Section: Discussionmentioning
confidence: 99%